2022
DOI: 10.1186/s13102-022-00491-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study on relationships between physical function and psychological readiness to return to sport after anterior cruciate ligament reconstruction

Abstract: Background Information about specific factors of physical function that contribute to psychological readiness is needed to plan rehabilitation for a return to sports. The purpose of this study was to identify specific physical functions related to the psychological readiness of patients aiming to return to sports 6 months after reconstruction. We hypothesized that the knee strength is a factor related to the Anterior Cruciate Ligament–Return to Sport after Injury scale (ACL-RSI) cutoff score fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Previous studies investigated the relationship between psychological readiness and functional performance [ 13 , 25 , 26 ]. The ACL-RSI score demonstrated to be a reliable scoring scale while evaluating psychological readiness for return to sports after ACL reconstruction [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies investigated the relationship between psychological readiness and functional performance [ 13 , 25 , 26 ]. The ACL-RSI score demonstrated to be a reliable scoring scale while evaluating psychological readiness for return to sports after ACL reconstruction [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by McPherson et al, patients who underwent ACL re-rupture trended toward lower ACL-RSI scores [ 19 ], while according to Sadeqi et al, ACL-RSI score ≥ 60 months after surgery is a reliable predictor of return to preinjury sport [ 27 ]. According to the study by Aizawa et al, in our case series, we considered 60 as a cut-off value to evaluate psychologic readiness to return to sport six months after surgery [ 13 ]. Webster et al followed up with 635 athletes 12 months after ACL reconstruction, and observed that greater limb symmetry while performing a single-legged hop for distance positively correlates with the ACL-RSI score [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation between jumping ability and subjective perception has been previously analyzed [ 15 , 16 , 17 , 18 ]. According to our findings, 12 months after surgery, weak positive correlation was reported between drop jump LSI and Tegner activity level.…”
Section: Discussionmentioning
confidence: 99%
“…difficulty returning to sport or have low ACL-RSI. 1,7 It should also be kept in mind that the ACL-RSI is an assessment measure that may be influenced by the personality of each patient. In addition, it is not yet clear how to improve ACL-RSI.…”
Section: Limitationsmentioning
confidence: 99%